Can a Rural bank Truly Be Protected from Occupational Fraud? An Inquiry into Anti-Fraud Strategies at PT BPR Danagung Bakti Yogyakarta - Maitsa Zharfa Hana; Hendi Yogi Prabowo (Proceeding International Conference on Accounting and Finance, 2025)
The trend of fraud problems that led to the decline in the number of rural bank prompted the Financial Services Authority (OJK) to establish a book published in 2022 containing the Financial Services Authority Regulation (POJK) for the implementation of a specific anti-fraud strategy for rural bank. This study was conducted at PT BPR Danagung Bakti Yogyakarta to determine the mechanism for implementing the implemented anti-fraud strategy, including prevention, detection, disclosure, and follow-up in minimizing occupational fraud. The study was conducted using a qualitative approach, a case study method, and data collection techniques through interviews with selected informants according to the specified criteria. The results of the study showed that the mechanism of the anti-fraud strategy applied is in accordance with the OJK’s Anti-Fraud Strategy Guide for rural bank, although there are shortcomings and obstacles that still need to be improved in its implementation.